Feasibility of a lateral flow test for neurocysticercosis using novel up-converting nanomaterials and a lightweight strip analyzer. - Paul L A M Corstjens; Claudia J de Dood; Jeffrey W Priest; Hans J Tanke; Sukwan Handali; Cysticercosis Working Group in Peru (Public Library of Science (PLoS), 2014)
Neurocysticercosis is a frequent parasitic infection of the human brain, occurring in most of the world, and requires imaging of the brain to diagnose. To determine the burden of disease and to simplify diagnosis, a field-friendly rapid lateral flow (LF) based antibody screening test was developed. The assay utilizes novel nano-sized up-converting phosphor (UCP) reporter particles in combination with a portable lightweight analyzer and detects antibodies in serum samples reactive with bacterial-expressed recombinant (r) T24H, a marker for detecting neurocysticercosis cases. Three sequential flow steps allow enrichment of antibodies on the Test (T) line and consecutive binding of protein-A coated UCP reporter particles. Antibody binding was determined by measuring 550 nm emission after excitation of the UCP label with a 980 nm infrared (IR) diode. Clinical sensitivity and specificity of the assay to detect cases of human neurocysticercosis with 2 or more viable brain cysts were 96% and 98%, respectively, using a sample set comprised of sera from 63 confirmed cases and 170 healthy parasite-naïve non-endemic controls.Proof-of-principle, of a rapid UCP-LF screening assay for neurocysticercosis was demonstrated. The assay utilized bacterial-expressed rT24H as a potential alternative for baculovirus-expressed rT24H. Performance of the UCP-LF assay was excellent, although further studies need to confirm that bacterial expressed antigen can entirely replace previously used baculovirus antigen. In addition, the increasing availability of commercial sources for UCP reporter materials as well as the accessibility of affordable semi-handheld scanners may allow UCP-based bioanalytical systems for point-of-care to evolve at an even faster pace.